1981
DOI: 10.1111/j.1348-0421.1981.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Bacterial Spore Coat: IX. The Role of Surface Charge in Germination of Bacillus megaterium Spores

Abstract: The surface charge of Bacillus megaterium QM B 1551 spores was estimated to be negative, -0.2 and -0.4 t-teq(mg by colloidal titration using glycol chitosan (GCh) and methylglycol chitosan (MGCh), respectively, as positive colloids. MGCh, which reacts with all of the negatively charged groups including carboxylate, inhibited the second stage of the germination to result in semirefractile spores, but GCh, which reacts only with strong acidic groups such as phosphate, did not. The spores produced in a medium wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Methods of removing one or both spore coats have been described in detail by Nishihara et al (141)(142)(143). Coats may be extracted by using 2-mercaptoethanol, sodium lauryl (dodecyl) sulfate, dithiothreitol (DTT), and urea.…”
Section: Sporulationmentioning
confidence: 99%
“…Methods of removing one or both spore coats have been described in detail by Nishihara et al (141)(142)(143). Coats may be extracted by using 2-mercaptoethanol, sodium lauryl (dodecyl) sulfate, dithiothreitol (DTT), and urea.…”
Section: Sporulationmentioning
confidence: 99%
“…Probably the most detailed approach to studying resistance of spores has involved the use of spore coatless forms (46, 62, 63, 69, 82, 88-91, 93, 124, 126, 132, 189, 194, 212, 224-228, 231, 237). Methods of removing one or both spore coats have been described in detail by Nishihara et al (141)(142)(143). Coats may be extracted by using 2-mercaptoethanol, sodium lauryl (dodecyl) sulfate, dithiothreitol (DTT), and urea.…”
Section: Sporulationmentioning
confidence: 99%
“…The slightly modified method of Watanabe & Takesue (1976) was used. Instead of protamine sulphate, GCh and MGCh (Wako Pure Chemical Corp.) were used as positive colloids, since Nishihara et al (1981) reported that titration values were estimated to be higher with protamine sulphate than with MGCh. An excess amount of the colloid (0.005 M, 5 ml) was added to an appropriate concentration of spores (20-30 mg per 2 ml) and the mixture was adjusted to the required pH with 0.05 M-HCI or 0.05 M-NaOH.…”
Section: Y a N D 0 And T T S U Z U K Imentioning
confidence: 99%
“…After incubation at room temperature for 20 min, the uncombined colloid was back-titrated with 0-0025 M-potassium polyvinyl sulphate (Wako Pure Chemical Corp.) using toluidine blue as the indicator. A sharp end-point with MGCh was obtained by removing the spores by centrifuging the titration mixture and adjusting the pH of the supernatant to 2.5 with 0.05 M-HCI before titration, according to the method of Nishihara et al (1981).…”
Section: Y a N D 0 And T T S U Z U K Imentioning
confidence: 99%
See 1 more Smart Citation